0119 Effects of Total Sleep Deprivation on Performance on a Continuous Performance Matching Task. (25th May 2022) - Hudson, Amanda; Hinson, John; Whitney, Paul; Lawrence-Sidebottom, Darian; Van Dongen, Hans; Honn, Kimberly
Abstract: Introduction: Tasks requiring individuals to identify specific stimuli may create response/non-response conflict, which may impair performance depending on stimulus feature overlap. Whether sleep deprivation interacts with such impairment is unknown. We investigated the effects of total sleep deprivation (TSD) on stimulus identification in a continuous performance matching task (CPMT). Methods: N=85 adults (ages 21–40; 50f) completed a 4-day laboratory study with 10h baseline sleep (22:00–08:00), a 38h acute TSD or 10h sleep opportunity (control condition), and 10h recovery sleep. The 6min CPMT was administered every 2–4h during wakefulness. Participants completed 300 trials where a 3-digit number was flashed on the screen for 100ms. They were instructed to respond (mouse-click) within 900ms, but only if the number was the same as the preceding number (i.e., a repeat); for all other trials a response was to be withheld. The 5 daytime testing sessions (09:00–21:00) at baseline (day 2) and after TSD/control (day 3) were used for analysis. Trials were classified based on number of digits matching the preceding trial (stimulus feature overlap): none (180 trials), one (30 trials), two (near-repeat; 30 trials), or all (repeat; 60 trials). Hit and false alarm (FA) rates were analyzed with mixed-effects ANOVA for day, condition, trial type, and their interactions. Mean response time (MRT) was analyzed equivalently for repeat trials only. Results: Hit rate declined from day 2 to day 3 in the TSD group (F[1, 83]=0.15, p<0.001), but not the control group (F[1, 83]=0.018, p=0.335). Though FA rate was low overall (<0.06), FA frequency was higher on trials with greater stimulus feature overlap. FA rate increased on day 3 for the TSD group (all p<0.004), especially for near-repeats (F[1, 415]=-0.014, p<0.001). Changes in MRT were statistically significant, but negligible (<20ms). Conclusion: Our results suggest that greater stimulus feature overlap on the CPMT was associated with greater costs required to resolve conflict. Sleep deprivation exacerbated these costs. Interpretation is limited however, because a response was not required for non-repeat trials. Implementing a two-alternative forced choice version of the task in future TSD studies would address this limitation. Support (If Any): PRMRP W81XWH-16-1-0319 and W81XWH-20-1-0442